Professional Identity and Trans-Perspective of Professional Development of Future Teachers - E. V. Lebedeva (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article presents a theoretical analysis of the problem of formation of professional identity in conditions of uncertainty and increasing multidimensionality of professional and educational space. The attention is focused on the fact that the dynamics of social processes is expressed in changing the requirements for the content and quality of work, the complexity of professional training. The multifactorial nature of professional development leads to the complication of the strategy of building a professional trans-perspective and requires a specially organized acmeological support of the identification process at the stage of vocational education. Within the theoretical review the definition of professional identity with the description of its structure is given, the author’s definition of professional trans-perspective is proposed. An important part of the article is the results of an empirical study of the features of professional identity and professional trans-perspective of students who are future teachers of vocational training. The interrelation of the main characteristics of professional trans-perspective - length, event density with indicators of professional identity: maturity, formation, activity of professional position, educational and professional plans - is revealed. Thus, the characteristics of professional identity can be considered as predictors for predicting a person’s professional future. In the final part, it is proposed to intensify the work on the development of professional identity of second-year students by supplementing the curriculum with elective modules aimed at the deficit aspects of professional self-determination.